Diet in secondary prevention: the effect of dietary patterns on cardiovascular risk factors in patients with cardiovascular disease: a systematic review and network meta-analysis - Bonekamp, N. E.; Cruijsen, E.; Geleijnse, J. M.; Winkels, R. M.; Visseren, F. L. J.; Morris, P. B.; Koopal, C. (Nutrition journal, 2024)
Background Improving dietary habits is a first-line recommendation for patients with cardiovascular disease (CVD). It is unclear which dietary pattern most effectively lowers cardiovascular risk factors and what the short- and long-term effects are. Therefore, this network meta-analysis compared the effects of popular dietary patterns on cardiovascular risk factors in patients with established CVD. Methods A systematic search of PubMed, Embase, the Cochrane library, SCOPUS and Web of Science was conducted up to 1 April 2023. Randomized controlled trials (RCTs) comparing the effect of popular dietary patterns (Mediterranean, moderate carbohydrate, low glycemic index, low-fat and minimal dietary intervention) on cardiovascular risk factors (body weight, systolic blood pressure, lipids) in CVD populations were selected. A random-effects network meta-analysis was performed. Results Seventeen RCTs comprising 6,331 participants were included. The moderate carbohydrate diet had the most beneficial effect on body weight (-4.6 kg, 95%CrI -25.1; 15.8) and systolic blood pressure (-7.0 mmHg 95%CrI -16.8; 2.7) compared to minimal intervention. None of the included dietary patterns had a favorable effect on low-density lipoprotein cholesterol. After 12 months, the effects were attenuated compared to those at < 6 months. Conclusions In this network meta-analysis of 17 randomized trials, potentially clinically relevant effects of dietary interventions on CV risk factors were observed, but there was considerable uncertainty due to study heterogeneity, low adherence, or actual diminished effects in the medically treated CVD population. It was not possible to select optimal dietary patterns for secondary CVD prevention. Given recent clinical trials demonstrating the potential of dietary patterns to significantly reduce cardiovascular event risk, it is likely that these effects are effectuated through alternative physiological pathways.